Discriminatory Indices of Typing Methods for Epidemiologic Analysis of Contemporary Staphylococcus aureus Strains. Issue 37 (September 2015) - Rodriguez, Marcela; Hogan, Patrick G.; Satola, Sarah W.; Crispell, Emily; Wylie, Todd; Gao, Hongyu; Sodergren, Erica; Weinstock, George M.; Burnham, Carey-Ann D.; Fritz, Stephanie A.; Yagupsky., Pablo
<x xml:space="preserve">Abstract</x> Abstract Historically, a number of typing methods have been evaluated for Staphylococcus aureus strain characterization. The emergence of contemporary strains of community-associated S. aureus, and the ensuing epidemic with a predominant strain type (USA300), necessitates re-evaluation of the discriminatory power of these typing methods for discerning molecular epidemiology and transmission dynamics, essential to investigations of hospital and community outbreaks. We compared the discriminatory index of 5 typing methods for contemporary S. aureus strain characterization. Children presenting to St. Louis Children's Hospital and community pediatric practices in St. Louis, Missouri (MO), with community-associated S. aureus infections were enrolled. Repetitive sequence-based PCR (repPCR), pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), staphylococcal protein A (spa), and staphylococcal cassette chromosome (SCC) mec typing were performed on 200 S. aureus isolates. The discriminatory index of each method was calculated using the standard formula for this metric, where a value of 1 is highly discriminatory and a value of 0 is not discriminatory. Overall, we identified 26 distinct strain types by repPCR, 17 strain types by PFGE, 30 strain types by MLST, 68 strain types by spa typing, and 5 strain types by SCCmec typing. RepPCR had the highest discriminatory index (D) of all methods (D = 0.88), followed by spa typing (D = 0.87), MLST (D = 0.84), PFGE (D = 0.76), and SCCmec typing (D = 0.60). The method with the highest D among MRSA isolates was repPCR (D = 0.64) followed by spa typing (D = 0.45) and MLST (D = 0.44). The method with the highest D among MSSA isolates was spa typing (D = 0.98), followed by MLST (D = 0.93), repPCR (D = 0.92), and PFGE (D = 0.89). Among isolates designated USA300 by PFGE, repPCR was most discriminatory, with 10 distinct strain types identified (D = 0.63). We identified 45 MRSA isolates which were classified as identical by PFGE, MLST, spa typing, and SCCmec typing (USA300, ST8, t008, SCCmec IV, respectively); within this collection, there were 5 distinct strain types identified by repPCR. The typing methods yielded comparable discriminatory power for S. aureus characterization overall; when discriminating among USA300 isolates, repPCR retained the highest discriminatory power. This property is advantageous for investigations conducted in the era of contemporary S. aureus infections.